Di peternakan penulis, Alastair Smith ; ilustrator, Justine Torode ; alih bahasa, Edia Permata ; editor, Margaretha Hutauruk Eddy, Merry Maida, Rara Tanjung Hidayat - SMITH, Alastair; Torode, Justine; Permata, Edia; Eddy, Margaretha Hutauruk; Hidayat, Rara Tanjung (Erlangga, 2003)
[16] hlm ilus 23 cm